Uporaba GPS-tehnike v geodetski izmeri - Kvas, Damjan (Geodetski vestnik, 1998)
This paper presents the current situation and future possibilities of using GPS techniques in geodetic surveys. The surveying techniques and basic characteristics are listed, as well as certain advantages and shortcomings of the use of GPS
Keywords: geodezija; GPS; merjenja; Slovenija